Structuring Discretion: The Association Between Law Enforcement Policies and Arrests of Children in Florida - Novak, Abigail (Crime & delinquency, 2024)
Thousands of children are arrested annually in the United States, and little is known about law enforcement policies regarding the arrest of children. The goal of this study was to examine the association between law enforcement policies pertaining to the arrest of children and arrests involving children in the state of Florida, the largest state in the U.S. that lacks a minimum age for juvenile court jurisdiction. Policies pertaining to the arrest of children were obtained from 215 law enforcement agencies, serving 95% of Florida’s population. Results indicated policies were not associated with arrests involving children, suggesting less-discretionary policies may be needed to reduce arrests for children in states lacking minimum ages for juvenile court jurisdiction.